Analisis Faktor-Faktor Yang Mempengaruhi Perilaku Disfungsional Auditor - Limanto, Melinda; Sukartha, I Made (E-Jurnal Akuntansi; Vol 27 No 2 (2019)DO - 10.24843/EJA.2019.v27.i02.p02, 2019)
This study aims to obtain empirical evidence of the influence of time budger pressure, machiavellian , internal locus of control, and organizational comitment on auditor’s dysfungsional behavior. Auditor’s dysfungsional behavior is an behavior of auditor that reduces audit quality and causes the audit process to fail. The study was conducted at the R I   BPKP Representative of Bali Province in 2019. Respondents in this study were determined  using the saturated sample method. Data collection using the questionnaire method. The data  analysis technique used is multiple linear regression. The results showed time budget pressures, and machiavellian traits had a positive effect on auditor dysfunctional behavior.   Internal locus of control variables, and organizational commitment negatively affect auditor dysfunctional behavior. Keywords : Dysfungsional, machiavellian, internal control, comitment